Assessing of soil aggregate stability: the sand-correction and its relevance - Huisz, Andrea (Acta Agraria Debreceniensis, 2009)
Soil structure and changes in its quality caused by Maize stem (1), Wheat straw (2) and Maize stem & wheat straw (3) addition were assessed by three aggregate-stability indices. We observed that the NSI index formula proposed by Six et al. (2000) was nonsensitive to the changes in soil structure caused by the investigated organic matter addition. Furthermore it overestimates the aggregate-stability of the investigated silty sandy loam soil. Therefore we proposed a new modified NSI formula which is sensitive to the questionable treatments and that resulted in a morerealistic NSI data. The most sensitive index to differences of the investigated treatments were the Mean weight diameter (MWD) proposed by van Bavel (1953, in Kemper és Rosneau, 1986).